2021
DOI: 10.3389/fpsyg.2020.572100
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cybervictimization and Non-suicidal Self-Injury in Chinese Adolescents: A Moderated-Mediation Model

Abstract: The present study investigated the mediating role of negative emotion in the relationship between cybervictimization and non-suicidal self-injury (NSSI), and the moderating role of friendship quality in the indirect relationship. This model was tested with 1,326 Chinese adolescents who suffered from cyberbullying in the last 1 year; 727 were boys and 591 were girls, and their mean age was 13.67 years (SD = 1.34, range 11–17). Participants filled out questionnaires regarding cybervictimization, negative emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…ES would enhance the effects of MPA on anxiety. Furthermore, in agreement with the findings of Wang et al [ 62 ], the results also demonstrated a positive correlation between ES and CR. It is clear from the results of this study that there are both differences and coexistences between CR and ES, and that the rational use of both can truly reflect the ability of emotion regulation [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…ES would enhance the effects of MPA on anxiety. Furthermore, in agreement with the findings of Wang et al [ 62 ], the results also demonstrated a positive correlation between ES and CR. It is clear from the results of this study that there are both differences and coexistences between CR and ES, and that the rational use of both can truly reflect the ability of emotion regulation [ 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although these studies have discussed the direct role of negative life events in the onset of NSSI in adolescents, it is important to view and understand the issue of NSSI in adolescents from a more comprehensive perspective, considering that the development of the adolescent stage may involves the moderating, mediating role of negative emotions, friendship quality, and other factors. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Although these studies have discussed the direct role of negative life events in the onset of NSSI in adolescents, it is important to view and understand the issue of NSSI in adolescents from a more comprehensive perspective, considering that the development of the adolescent stage may involves the moderating, mediating role of negative emotions, friendship quality, and other factors. 17,18 According to General Strain Theory (GST), negative stimuli from multiple sources can lead to negative affective states and cause individuals to adopt violent or deviant behaviors as coping strategies for negative emotions. 19 In addition, the experiential avoidance model (EAM) has suggested that the primary function of NSSI is to avoid negative emotions that the individual does not want to experience, and most studies also consider NSSI to be a nonadaptive way of coping to alleviate negative emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Friendship quality is an important index to measure friendships, which reflects the level of support, company, and conflict between friends (Van Schalkwyk et al, 2017 ; Wang et al, 2021 ). Access to epidemic information may have an impact on life satisfaction through the mediating role of perceived stress, but this is not true of all individuals, so the process by which access to epidemic information affects life satisfaction may be moderated by other factors.…”
Section: Introductionmentioning
confidence: 99%